Analisis Partisipasi Anggaran, Akuntansi Pertanggungjawaban Dan Komitmen Organisasi Terhadap Kinerja Manajerial Pada Sekolah Di Kecamatan Baki Kabupaten Sukoharjo - Suprihati Suprihati; Nur Fatihatul Jannah; Johny Subarkah (ITB AAS INDONESIA, 2023)
This study aims to determine the effect of budgetary participation, accountability accounting and organizasion commitment on managerial performance. This research is a questionnaire. The subjects in this study were all teachers and employees of Baki District, Sukoharjo Regency. The population in the study amounted to 743 with a predetermined sample using the hair formula which got 150 results. The data analysis technique used validity and reliability tests. The classical assumtion test uses normality, multicollinearity and heteroscedasticity tests. Testing the hypothesis of this study using multiple linier regression analysis, F test. T test, and test the coefficient of determination. The results of the study indicate that simultaneously responsibility accounting budget partisipation and managerial performance have a significant effect on managerial performance. As well as partially responsibility accounting has a significant effect on managerial performance, then budgetary participation and organization commitment have no effect on managerial performance.